Water in bacterial biofilms: pores and channels, storage and transport functions. (4th May 2022) - Quan, Kecheng; Hou, Jiapeng; Zhang, Zexin; Ren, Yijin; Peterson, Brandon W.; Flemming, Hans-Curt; Mayer, Christian; Busscher, Henk J.; van der Mei, Henny C.
Abstract: Bacterial biofilms occur in many natural and industrial environments. Besides bacteria, biofilms comprise over 70 wt% water. Water in biofilms occurs as bound- or free-water. Bound-water is adsorbed to bacterial surfaces or biofilm (matrix) structures and possesses different Infra-red and Nuclear-Magnetic-Resonance signatures than free-water. Bound-water is different from intra-cellularly confined-water or water confined within biofilm structures and bacteria are actively involved in building water-filled structures by bacterial swimmers, dispersion or lytic self-sacrifice. Water-filled structures can be transient due to blocking, resulting from bacterial growth, compression or additional matrix formation and are generally referred to as "channels and pores." Channels and pores can be distinguished based on mechanism of formation, function and dimension. Channels allow transport of nutrients, waste-products, signalling molecules and antibiotics through a biofilm provided the cargo does not adsorb to channel walls and channels have a large length/width ratio. Pores serve a storage function for nutrients and dilute waste-products or antimicrobials and thus should have a length/width ratio close to unity. The understanding provided here on the role of water in biofilms, can be employed to artificially engineer by-pass channels or additional pores in industrial and environmental biofilms to increase production yields or enhance antimicrobial penetration in infectious biofilms.